Accuracy of a New Platelet Count System (PLT-F) Depends on the Staining Property of Its Reagents. - Atsushi Wada; Yuri Takagi; Mari Kono; Takashi Morikawa (PLoS ONE, 2015)
Platelet count is essential for the diagnosis and management of hemostasis abnormalities. Although existing platelet count methods installed in common hematology analyzers can correctly count platelets in normal blood samples, they tend to miscount platelets in some abnormal samples. The newly developed PLT-F channel in the XN-Series hematology analyzer (Sysmex) has been reported to be a reliable platelet count system, even in abnormal samples. However, how the PLT-F platelet counting system achieves such accuracy has not been described in scientific articles.Isolated platelets, erythrocytes, and fragmented erythrocytes were examined using an automated hematology analyzer. The samples were labeled by combining PLT-F reagents and anti-CD62p, CD63, Grp75, Calreticulin, CD41, or CD61 antibody, and analyzed using confocal laser scanning microscopy or flow cytometry.The PLT-F system correctly discriminated platelets in erythrocytes. Its reagents strongly stained some intraplatelet organelles labeled with anti-Grp75, but only faintly stained the plasma membrane of both platelets and erythrocytes. Microscopic observation and flow cytometric examination revealed that all of these strongly stained cells were also labeled with platelet-specific anti-CD41 and anti-CD61 antibodies.This study revealed that the staining property of the PLT-F reagents, by which platelets and fragmented erythrocytes are clearly distinguished, contributes to the platelet-counting accuracy of the PLT-F system.